Short-term biotic removal of dissolved organic nitrogen (DON) compounds from soil solution and subsequent mineralisation in contrasting grassland soils. (May 2016) - Carswell, A.M.; Hill, P.W.; Jones, D.L.; Blackwell, M.S.A.; Johnes, P.; Chadwick, D.R.
Abstract: Cycling of low molecular weight dissolved organic nitrogen compounds constitutes an important component of soil organic matter turnover in soils. We determined how rapidly grassland soils can cycle urea, compared to the amino acidl -alanine, and the peptidel -trialanine. Using naturally occurring concentrations of 14 C-labelled compounds the rates of removal from soil solution and subsequent mineralisation were measured. Biotic removal of all three compounds and subsequent mineralisation to CO2 occurred within minutes. This research has demonstrated, for the first time, the potential for rapid removal of urea at low concentrations by the soil microbial biomass. Highlights: 14 C-urea cycling was examined in three grassland soils over short-timescales. The key urea cycling processes examined were biotic removal and mineralisation. Microbial removal from the soil solution and subsequent mineralisation of urea occurred within minutes.